Intelligent controlled shunt active power filter for voltage and current harmonic compensation in microgrid system. (19th May 2018) - Tan, Kuang-Hsiung; Lin, Faa-Jeng; Chen, Jun-Hao; Chang, Yung-Ruei
ABSTRACT: An integrated microgrid with a novel shunt active power filter (APF) using Elman neural network (ENN) is proposed in this study. The microgrid consists of a storage system, a photovoltaic (PV) system, the shunt APF, a linear load, and a nonlinear load. Moreover, the master/slave control algorithm is adopted in the microgrid. The storage system, which is considered as the master unit, is adopted to control the active and reactive power outputs (P/Q control) in grid-connected mode and the voltage and frequency of the microgrid (V/f control) in islanded mode. Furthermore, the PV system is considered as the slave unit to implement P/Q control in both grid-connected and islanded modes. In addition, the proposed shunt APF possesses dual functions of voltage and current harmonic compensation for microgrid under voltage harmonic propagation and nonlinear load to reduce the voltage and current total harmonic distortions (THD) effectively. Additionally, an ENN controller is adopted in the proposed shunt APF to improve the transient and steady-state responses of DC-link voltage during the switching between the grid-connected mode and islanded mode. Finally, some simulation results are provided to verify the feasibility and the effectiveness of the integrated microgrid with the intelligent controlled shunt APF.